2019
DOI: 10.3390/en12091713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Energy in the Production of Sweet Sorghum (Sorghum Bicolor (L.) Moench) under Different Production Systems

Abstract: The growing global demand for energy and the reduction of energy based on oil are driving the search for new sources of energy that are environmentally friendly. To achieve this goal, it is also necessary to optimize the related processes. In this study, the behavior of the agronomic parameters of, and the energy invested in, production systems based on a new variety of sweet sorghum (Sorghum bicolor (L.) Moench) called ROGER were determined to define the optimal production conditions. To this end, three metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
0
11
1
Order By: Relevance
“…Our results corroborated that the N level and the year of cultivation exerted important effects on durum wheat and sorghum grain production. Cabrera-Ariza et al (2019 andDíaz et al (2018) reported that crop management had important effects on sorghum energy balance. The energy produced varied between 126 and 365 GJ ha -1 depending on crop management, hybrid and growing season.…”
mentioning
confidence: 99%
“…Our results corroborated that the N level and the year of cultivation exerted important effects on durum wheat and sorghum grain production. Cabrera-Ariza et al (2019 andDíaz et al (2018) reported that crop management had important effects on sorghum energy balance. The energy produced varied between 126 and 365 GJ ha -1 depending on crop management, hybrid and growing season.…”
mentioning
confidence: 99%
“…We compared the obtained results with foreign achievements of sweet sorghum cultivation in the North Caucasus, China, Poland, and Mexico [53][54][55][56]. The energy inputs in sweet sorghum production depend on technology, soil, and climate conditions.…”
Section: International Experiencementioning
confidence: 99%
“…Fertilizer inputs are low compared to foreign practice. If we had 6.6 GJ/ha, that selected countries had the following figures, GJ/ha: China, from 21 to 26 [55]; Poland, around 16.5 [22]; and Mexico, around 15 [53].…”
Section: Energy Efficiency Of Sweet Sorghummentioning
confidence: 99%
See 1 more Smart Citation
“…Energy crops of algae include chlorella, dunaliella, botryococcus, etc. Today, one of the most promising energy crops is sorghum [8,9].…”
Section: Introductionmentioning
confidence: 99%